Fluorescence visualization for cancer DETECTION: EXPERIENCE and perspectives - Yaroslav Kravchenko; Kateryna Sikora; Andrew Awuah Wireko; Mykola Lyndin (Heliyon, 2024)
The current review focuses on the latest advances in the improvement and application of fluorescence imaging technology. Near-infrared (NIR) fluorescence imaging is a promising new technique that uses non-specific fluorescent agents and targeted fluorescent tracers combined with a dedicated camera to better navigate and visualize tumors. Fluorescence-guided surgery (FGS) is used to perform various tasks, helping the surgeon to distinguish lymphatic vessels and nodes from surrounding tissues easily and quickly assess the perfusion of the planned resection area, including intraoperative visualization of metastases. The results of the insertion of fluorescence visualization as an auxiliary method to cancer detection and high-risk metastatic lesions in clinical practice have demonstrated enthusiastic results and huge potential. However, intraoperative fluorescence visualization must not be considered as a main diagnostic or treatment method but as an aid to the surgeon. Thus, fluorescence study does not dispense the diagnostic gold standards of benign or malignant tumors (conventional examination, biopsy, ultrasonography and computed tomography, etc.) and can be done usually during intraoperative treatment. Moreover, as fluorescence surgery and fluorescence diagnostic techniques continue to improve, it is likely that they will evolve towards targeted fluorescence imaging probes that will increasingly target a specific type of cancer cell. The most important point remains the search for highly selective messengers of fluorescent labels, which make it possible to identify tumor cells exclusively in the affected organs and indicate to surgeons the boundaries of their spread and metastasis.